"Lapland's Roadway": German Photography and Experience of the European Far North in the Second World War. (2nd January 2019) - Seitsonen, Oula; Herva, Vesa-Pekka; Koponen, Tuuli
Abstract: This article examines photographs illustrating the German war effort in Finnish Lapland during the Second World War. We will analyze the German photographic representation of Lapland from the perspective of how the Germans portrayed and experienced this northern land, with a focus on Fahrbahn Lappland (Lapland's Roadway), a coffee-table book by the German photojournalist Mabre (Max Martin Brehm). It affords interesting insights into German perceptions of and engagements with the Far North of the European world. The photographs in Fahrbahn reflect a sense of dislocation on the one hand and an attempt to neutralize the physically and mentally threatening northern wilderness on the other. In addition to capturing the "spirit" of the German experience of Lapland through his photographs, Mabre's work resonates with a dystopian tradition of representing the North of Europe dating back to the early modern period and beyond. It presents Lapland as a "blank slate" by distancing the locals from the view and showing the region as a virtually unoccupied periphery on the fringe of the modern world. This can perhaps be understood as making "mental groundwork" for the anticipated Nazi German rule in the North of Europe after the war.